A new step in understanding stem cell mobilization in patients with Fanconi anemia: A bridge to gene therapy. Issue 1 (9th November 2021) - Diana, Jean‐sébastien; Manceau, Sandra; Leblanc, Thierry; Magnani, Alessandra; Magrin, Elisa; Bendavid, Matthieu; Couzin, Chloe; Joseph, Laure; Soulier, Jean; Cavazzana, Marina; Lefrère, Francois
Abstract: Background: Fanconi anemia (FA) is an inherited disorder characterized clinically by congenital abnormalities, progressive bone marrow failure (BMF), and a predisposition to malignancy. Gene therapy (GT) of FA, via the infusion of gene‐corrected peripheral blood (PB) autologous hematopoietic stem cells (HSCs), may constitute a cure for BMF. GT bypasses the donor restrictions and adverse events associated with allogenic HSC transplantation. However, adequate harvesting of PB‐HSCs is a crucial determinant of successful engraftment in gene therapy. Harvesting the low numbers of HSCs in patients with FA is particularly challenging. Study design and methods: This open‐label phase I/II trial evaluates the feasibility and safety of co‐administration of G‐CSF and plerixafor in patients with FA for the mobilization and harvesting of peripheral HSCs, intending to use them in a gene therapy trial. Patients with mutations in the FANCA gene received two subcutaneous injections of G‐CSF (6 μg/kg × 2/d from D1 to D8. Plerixafor (0.24 mg/kg/d) was administered 2 h before apheresis (from D5 onward). Results: CD34 + cells were mobilized for four patients quickly but transiently after the plerixafor injection. One patient had a CD34 + cell count of over 100/μl; the mobilization peaked 2 h after the injection and lasted for more than 9 h. There were no short‐term adverse events associated with the mobilization or harvesting procedures. Conclusion: Our data in patients with FA show that the mobilization of HSCs with G‐CSF and plerixafor is safe and more efficient in younger individuals without BMF.